Effectiveness of Using Information, Education, and Communication Flowchart Media in Implementation of Early Breastfeeding Initiation - Notarianti, Rizna; Fikawati, Sandra; Faradhila, Alifani Faiz (UI Scholars Hub, 2022)
Early initiation of breastfeeding (EIB) has many benefits for both the baby and the mother. However, in Bogor City, there are still many babies who do not get EIB when they are born (33.6%). The implementation of EIB is not optimal due to the absence of standard procedures to equalize its theory and perception. This study aimed to investigate the effectiveness of using Information, Education, and Communication (IEC) flowchart media concerning the standard procedure for EIB implementation in the Primary Health Care (PHC) in Bogor City. A quasi-experimental research was conducted on 58 midwives divided into the intervention and control groups. The intervention group was given IEC flowchart media, the EIB standard procedure, whereas the control group was given a brief explanation about EIB. The results indicated that the intervention group (96.0) had a higher average EIB implementation score than the control group (84.7). Furthermore, the success rate of EIB was higher in the intervention group (93.1%) than in the control group (20.7%). In conclusion, the IEC flowchart media is effectively used to optimize EIB implementation by midwives in the PHC in Bogor City.